Pengembangan model pembelajaran ICARE pada ekspansi kelas yang sesuai dengan kultur dan karakter siswa di SDN Gedongan 2 dan SDN Meri 2 Kota Mojokerto - Ahmad Jalalluddin Al-Mahali (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2017)
One model of learning that includes a series of learning experiences planned systematically arranged, operational, and targeted to help students master specific learning objectives is the expansion ICARE study model class. The purpose of the development of the learning model ICARE on the expansion of the class are: Produce learning model ICARE the expansion of classes in accordance with the culture and character of students at SDN Gedongan 2 and SDN Meri 2 Mojokerto From the results of this development can be concluded: 1) Products that are developed interesting for learning in the classroom in the classical and independently. 2) This product can ease the burden of teachers in teaching. 3) The results of expert validation and testing, the ICARE study model on the expansion of this class suitable for use in subjects Religious Education Islam.4) Products that are developed can increase students' motivation, and motivation is one of the conditions of implementation of productive learning model. 5) Products that are developed can improve ketuntaan study for students from three classes of trials increased mastery of grade V-A SDN Gedongan 2 Mojokerto average value Pre test 73.66 increase on the post test 87.80 while the percentage of completeness pre-test is a 75.61% increase to 92.68%. Students in grade VB SDN Gedongan 2 Mojokerto average value Pre test 70.49 increase on the post test 87.80 while the percentage of completeness pre-test is a 68.29% increase to 92.68% and fifth grade students of SDN Meri 2 Mojokerto in mind that the average value of Pre test 75.71 increases in post test 87.22 while the percentage of completeness pre-test is a 77.14% increase to 88.89%. Thus, it can be concluded that it is feasible for the dissemination media as a learning strategy.